Interstitial lung disease in anti-synthetase syndrome: Initial and follow-up CT findings. Issue 3 (March 2015) - Debray, Marie-Pierre; Borie, Raphael; Revel, Marie-Pierre; Naccache, Jean-Marc; Khalil, Antoine; Toper, Cécile; Israel-Biet, Dominique; Estellat, Candice; Brillet, Pierre-Yves
Abstract: Purpose: To describe the initial and follow-up CT features of interstitial lung disease associated with anti-synthetase syndrome (AS-ILD). Materials and methods: Two independent thoracic radiologists retrospectively analysed thin-section CT images obtained at diagnosis of AS-ILD in 33 patients (17 positive for anti-Jo1, 13 for anti-PL12, and three for anti-PL7 antibodies). They evaluated the pattern, distribution and extent of the CT abnormalities. They also evaluated the change in findings during follow-up (median 27 months; range 13–167 months) in 26 patients. Results: At diagnosis, ground-glass opacities (100%), reticulations (87%) and traction bronchiectasis (76%) were the most common CT findings. Consolidations were present in 45% of patients. A non-specific interstitial pneumonia (NSIP), organizing pneumonia (OP) or mixed NSIP-OP CT pattern were observed in 15 out of 33 (45%), seven out of 33 (21%) and eight out of 33 (24%) patients, respectively, whereas the CT pattern was indeterminate in three patients. During follow-up, consolidations decreased or disappeared in 11 out of 12 patients (92%), among which seven within the first 6 months, but honeycombing progressed or appeared in ten out of 26 patients (38%) and overall disease extent increased in nine out of 26 patients (35%). Conclusion: CT features at diagnosis of AS-ILD mainly suggest NSIP and OP, isolated or in combination. Consolidations decrease or disappear in most cases but the disease may progress to fibrosis in more than one third of patients.